Silereng: Sistik Ikan Lele Goreng Sebagai Alternatif Olahan Pangan Berbahan Dasar Ikan Lele di Desa Sumberadi, Kebumen, Jawa Tengah - Chalisty, Vian Dwi; Isnaeni, Laelatul; Isnaeni, Faul; Hidayat, Syarif; Nurrochim, Alvin; Mamluatunnajah, Ngafifah; Kholifah, Nur; Alqoroni, Moh Uwais; Nurdiana, Yuli; Rifa’i, Muhammad Mahmud; Nazila, Rokhmatun (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Sumberadi Village is one of the villages in Kebumen District, Kebumen Regency, Central Java Province. Sumberadi Village has several facilities managed by the village government, including catfish farming using the biofloc method. The biofloc method has advantages, including reducing water usage during cultivation, reducing water waste, and increasing catfish productivity. Catfish is a type of freshwater fish that is easy to cultivate and high in nutritional content. Catfish contain high protein and are rich in omega-3 fatty acids, vitamins, and minerals for children's growth and development. Catfish cultivation in Sumberadi Village usually results in the harvest being sold live or raw. Direct sales in live or raw conditions require that the catfish are sold out because they are not fresh if stored for a long time. If the sale of catfish is made into processed products, it can increase the selling price and become a superior product of Sumberadi Village. In addition, the Sumberadi Village community can also be more productive and increase entrepreneurial spirit and income by making processed catfish products. The purpose of implementing community service in Sumberadi Village is to increase community knowledge related to the potential and benefits of catfish for health and child development and increase community skills in processing catfish into fried catfish sistik. This community service activity was carried out in several stages, namely, surveys and location observations to approach village officials and the community, socialization with the village community, and the implementation of making fried catfish sistik. Based on the community service activities that have been carried out, it can be concluded that participants' knowledge and skills in making fried catfish sistik products have increased; participants can accept fried catfish cystic products produced as consumers in terms of taste, shape, and packaging